Development of the prototype concise safe systems checklist tool for general practice - Ian Litchfield; Rachel Spencer; Brian G. Bell; Anthony Avery; Katherine Perryman; Kate Marsden; Sheila Greenfield; Stephen Campbell (BMC, 2020)
Abstract Background In the course of producing a patient safety toolkit for primary care, we identified the need for a concise safe-systems checklist designed to address areas of patient safety which are under-represented in mandatory requirements and existing tools. This paper describes the development of a prototype checklist designed to be used in busy general practice environments to provide an overview of key patient safety related processes and prompt practice wide-discussion. Methods An extensive narrative review and a survey of world-wide general practice organisations were used to identify existing primary care patient safety issues and tools. A RAND panel of international experts rated the results, summarising the findings for importance and relevance. The checklist was created to include areas that are not part of established patient safety tools or mandatory and legal requirements. Four main themes were identified: information flow, practice safety information, prescribing, and use of IT systems from which a 13 item checklist was trialled in 16 practices resulting in a nine item prototype checklist, which was tested in eight practices. Qualitative data on the utility and usability of the prototype was collected through a series of semi-structured interviews. Results In testing the prototype four of nine items on the checklist were achieved by all eight practices. Three items were achieved by seven of eight practices and two items by six of eight practices. Participants welcomed the brevity and ease of use of the prototype, that it might be used within time scales at their discretion and its ability to engage a range of practice staff in relevant discussions on the safety of existing processes. The items relating to prescribing safety were considered particularly useful. Conclusions As a result of this work the concise patient safety checklist tool, specifically designed for general practice, has now been made available as part of an online Patient Safety Toolkit hosted by the Royal College of General Practitioners. Senior practice staff such as practice managers and GP partners should find it a useful tool to understand the safety of less explored yet important safety processes within the practice.